Sociologiceskij monitoring rukovoditelej organov ispolnitel'noj vlasti v oblasti fiziceskoj kul'tury i sporta - Vinogradov, P. A.; Okunkov, Ju. V. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The sociological group of Rossport has been carring out the interrogations of the regional directors heading physi-cal culture and sports in subjects of the Federation for many years. The last research was carried out in April, 2006. Estimating the social characteristics of the respondents, it is possible to assert, that the data received by the au-thors reflect the opinion and estimations of the experts of the highest level which carry out management of physical culture and sports in Russia.